2017
DOI: 10.1091/mbc.e16-05-0271
|View full text |Cite
|
Sign up to set email alerts
|

A microtubule bestiary: structural diversity in tubulin polymers

Abstract: Microtubules are long, slender polymers of αβ-tubulin found in all eukaryotic cells. Tubulins associate longitudinally to form protofilaments, and adjacent protofilaments associate laterally to form the microtubule. In the textbook view, microtubules are 1) composed of 13 protofilaments, 2) arranged in a radial array by the centrosome, and 3) built into the 9+2 axoneme. Although these canonical structures predominate in eukaryotes, microtubules with divergent protofilament numbers and higher-order microtubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 74 publications
3
118
0
Order By: Relevance
“…Importantly, microtubules with a non-13 protofilaments (e.g. 14 or 15 protofilaments) have also been found in diverse cell types across different species (Chaaban and Brouhard, 2017). However, we do not understand how protofilament number is regulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, microtubules with a non-13 protofilaments (e.g. 14 or 15 protofilaments) have also been found in diverse cell types across different species (Chaaban and Brouhard, 2017). However, we do not understand how protofilament number is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Tubulin purified from animal brains, which has been extensively used for biochemical and structural analyses, contains a mixture of different tubulin isotypes (Banerjee et al, 1988) and polymerizes into microtubules containing 9 to 16 protofilaments in vitro (Chaaban and Brouhard, 2017). Recent studies have described the purification and use of recombinant human tubulin and have shown differences in polymerization dynamics of microtubules assembled with different β-tubulin isotypes (Pamula et al, 2016; Vemu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…MTs are built of /-tubulin heterodimers that assemble longitudinally into protofilaments (PFs) and laterally into hollow cylinders. In vitro, MTs can form with various PF numbers, but in mammalian cells they mainly contain 13 PFs (Chaaban and Brouhard, 2017;Tilney et al, 1973). DCX strongly promotes nucleation and stabilisation of this physiological 13-PF architecture (Moores et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In living cells, stable MTs are mostly formed by the parallel arrangement of 13 PFs, whereas under laboratory conditions MTs ranging typically from 12 to 17 PFs can be obtained . The predominance of 13‐PF arrangements has been explained in the literature in terms of the “straight‐protofilament hypothesis,” which states that only the 13‐PF geometry allows PFs to run straight relative to the MT axis . As cytoskeletal components MTs exist in a continuously dynamic state of growing and shortening through the reversible association and dissociation of αβ‐tubulin heterodimers.…”
Section: Introductionmentioning
confidence: 99%
“…2 The predominance of 13-PF arrangements has been explained in the literature in terms of the "straight-protofilament hypothesis," which states that only the 13-PF geometry allows PFs to run straight relative to the MT axis. 3 As cytoskeletal components MTs exist in a continuously dynamic state of growing and shortening through the reversible association and dissociation of αβ-tubulin heterodimers. This dynamic behavior is controlled by the GTP/GDP exchange in the β-subunit of a MT end, while other GTP unit is tightly bound to α-tubulin and is nonexchangeable.…”
Section: Introductionmentioning
confidence: 99%